2008
DOI: 10.1016/j.physletb.2008.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Non-minimally coupled quintom model inspired by string theory

Abstract: In this paper we consider a quintom model of dark energy with a single scalar field T given by a Lagrangian which inspired by tachyonic Lagrangian in string theory. We consider non-minimal coupling of tachyon field to the scalar curvature, then we obtain the equation of state (EoS), and the condition required for the model parameters when ω crosses over −1.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…In contrast to Refs. (Cai et al, 2007b;Sadeghi et al, 2008;Li et al, 2005) here we do not need to add an extra term or a dimension-6 operator ⊔ ⊓T ⊔ ⊓T in the Lagrangian of tachyon field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Refs. (Cai et al, 2007b;Sadeghi et al, 2008;Li et al, 2005) here we do not need to add an extra term or a dimension-6 operator ⊔ ⊓T ⊔ ⊓T in the Lagrangian of tachyon field.…”
Section: Resultsmentioning
confidence: 99%
“…In Refs. (Cai et al, 2007b;Sadeghi et al, 2008) the Authors have been added an extra higher derivative term T ⊔ ⊓T in the square root part of the tachyonic Lagrangian and showed that crossing of the phantom divide occurs before reaching the tachyon potential asymptotically to its minimum. Considering a spatially-flat Friedmann-Robertson-Walker (FRW) metric,…”
Section: The Modelmentioning
confidence: 99%
“…Thus, one adds an extra term T 2T to the usual terms in the square root and the non-minimal coupling Rf (T ) [119,227]: where M p is the reduced Planck mass. Action (6.29) can be brought to a simpler form for the derivation of the equations of motion by performing a conformal transformation g µν → f (T )g µν :…”
Section: A Model Inspired By String Theorymentioning
confidence: 99%
“…To this effect, a large variety of scalar field models are discussed in the literature including quintessence [8][9][10][11][12][13][14], K-essence [15,16], spintessence [17], a e-mail: mohdshahamu@gmail.com b e-mail: shibesh.math@gmail.com c e-mail: rmyrzakulov@gmail.com tachyon [18,19], quintom [20][21][22][23][24][25][26][27], chameleon [28][29][30][31] and many more. These models of the scalar field give the equation of state parameter w ≥ −1.…”
Section: Introductionmentioning
confidence: 99%